Analisis Pengaruh Harga, Kualitas Produk, dan Ulasan Konsumen Terhadap Keputusan Pembelian pada Platform Belanja Online Shopee: Studi Kasus Mahasiswa Universitas Negeri Medan - Viory Salsabila; Intan Jamilah; Refi Adiyaksa Harahap; Roberto Evanbert Ginting; Lasroha Limpaulus Purba; Andi Taufiq Umar (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This type of research is associative quantitative research which has the aim of analyzing partially or simultaneously the effect of price, product quality and consumer reviews on purchasing decisions on the Shopee online shopping platform at Medan State University. The sample used in this study was 40 respondents obtained using purposive sampling technique. Data collection was taken using a questionnaire via Google Form. The data analysis method uses validity test, reliability test, multiple linear regression analysis, t test and F test, and the coefficient of determination with computational data calculation and processing. The validity test results on the 20 instrument items used show rcount> rtable, and the Cronbach Alpha value> 0.6 so it can be concluded that the data obtained is valid and reliable. The results of hypothesis testing show that price and product quality do not have a positive influence on purchasing decisions on the Shopee platform, while consumer reviews show that there is a positive and significant influence on purchasing decisions on the Shopee platform at Medan State University with a tcount value = 4.513> ttable = 1.688 and a significance value of 0.000 <0.05. For simultaneous testing, it shows that there is an influence between price, product quality, and consumer reviews on purchasing decisions with a value of Fhitung> Ftabel = 18,983> 2.87 with a significance value = 0.000 < 0.05. As an implication of this research, there needs to be further research related to the effect of price and product quality using different dependent variables.